Kinetic, isothem and mechansim in paraquat removal by adsorption processes using different biochars - TOAN CHI NGUYEN (Lowland Technology International, 2020)
This study aimed to explore the isotherm, kinetic and mechanism of paraquat adsorption in aqueous solution by coconut fiber (CFB), corn cob (CCB), bagasse (BGB) and rice husk (RHB) biochars.The method for biochar characteristics are identified using SEM, BET, and FTIR. Kinetic and isotherm data are according to the Pseudo-second-order and Langmuir models. The biochars are arranged according to their capacity: CFB (12, 72 mg/g), CCB (10.27 mg/g), RHB (9.72 mg/g), BGB (7.79 mg/g) where specific surface area and pore volume determine adsorption capacity. The intraparticle diffusion model is used to assess the kinetic rate of the adsorption process, which indicates the rate constant of the external diffusion phase where Kip1 moves faster than the Kip2 and Kip3 phases. Film diffusion has a role in the adsorption process. Pore filling, diffusion, hydrogen bonding, π-π and electrostatic interactions contribute to the mechanism of adsorption. CFB has the highest adsorption capacity (12.72 mg/g), and can be an alternative adsorbent.